Electrophoresis Display

A high-density graft copolymer with phosphonic acid-based anchoring and ionic liquid residues, along with a surface cross-linking network, addresses chemical instability and manufacturing complexity in electrophoretic displays, achieving enhanced stability and reliability with improved charge capacity and high-resolution imaging.

KR103043236B1Active Publication Date: 2026-11-05NSPECTRA CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
KR1020260162534
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2026-08-28
Publication Date
2026-11-05
Estimated Expiration
2046-08-28

AI Technical Summary

Technical Problem

Conventional electrophoretic display technologies face issues with chemical instability, low surface coverage density, spontaneous aggregation, charge loss, and complex manufacturing processes, leading to reduced reliability and lifespan of electrophoretic particles.

Method used

The use of a high-density graft copolymer with phosphonic acid-based anchoring and ionic liquid residues, combined with a surface cross-linking network, to enhance dispersion stability, charge reliability, and simplify the manufacturing process.

Benefits of technology

The solution provides electrophoretic particles with improved chemical stability, increased charge capacity, long-term reliability, and high-resolution imaging, maintaining image clarity for over 10 hours without power and enhancing manufacturing yield by over 30%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 112026106081121-PAT00001
    Figure 112026106081121-PAT00001
  • Figure 112026106081121-PAT00002
    Figure 112026106081121-PAT00002
  • Figure 112026106081121-PAT00003
    Figure 112026106081121-PAT00003
Patent Text Reader

Abstract

The present invention relates to electrophoretic particles that perform stable behavior within a dispersion medium and a display device comprising the same. The electrophoretic particles of the present invention comprise a base particle having a hydroxyl group or a carboxyl group on its surface, a graft copolymer bonded thereto, and a surface crosslinking agent. The above graft copolymer contains, within a single molecule, phosphonic acid residues that form polydentate bonds with base particles, side-chain macromonomer units with a number average molecular weight of 500 to 5,000 that provide steric hindrance in non-polar media, and ionic liquid residues such as imidazolium salts. Additionally, the crosslinking agent chemically links the polymer main chains formed on the particle surface to form a shell cross-linking structure that envelops the entire particle. This hybrid network structure prevents shell detachment and maintains a stable charge state even under external electric field stress, enhancing particle dispersibility while providing excellent bistability and high-resolution images that maintain images for a long time even when the power is off.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to the technical field of charged particles for an electrophoretic display device and a method for manufacturing the same. Specifically, it relates to an electrophoretic particle and a display device technology comprising the same, which simultaneously improves the dispersion stability and charge reliability of the particle in a non-polar dispersion medium by applying a high-density graft copolymer containing a phosphonic acid-based strong anchoring mechanism and ionic liquid residues, and an inter-chain surface crosslinking network. Background Technology

[0002] Electrophoretic displays are a technology in which micro-particles charged within a fluid move by an electric field to form an image. They are attracting attention as next-generation low-power displays due to their bistability, which maintains the image even when the power is cut off, and high visibility similar to paper. The key factors determining the reliability of such displays are dispersion stability, which prevents electrophoretic particles from clumping within the dispersion medium, and charge control capability, which enables them to respond quickly and precisely according to the applied voltage. The initial technology, US 7,457,028 B2, proposed a method of modifying the particle surface with a basic silane coupling agent to improve the response speed of the particles; however, due to the lack of long-term dispersion of the particles in non-polar solvents, a problem of shortened lifespan caused by particle aggregation occurred.

[0003] Subsequently, living radical polymerization technology, which involves growing polymer chains directly on the particle surface, was attempted through JP 2013-156381 A. However, due to the structural limitations of the introduced polymer requiring simultaneous dispersion and charging functions, a trade-off problem arose in which it was difficult to independently control the amount of charge and the dispersion ability. Additionally, in US 8,934,165 B2, silicone-based functional groups were introduced to improve compatibility with silicone oil, but steric hindrance caused by the bonding of macropolymer chains resulted in the formation of bare spots that could not completely cover the particle surface, leading to irregular charge behavior of the particles.

[0004] The prior art US 10,597,541 B2, designed to solve these problems, employs a method of sequentially bonding three components—a dispersion block copolymer, a low-molecular-weight nonpolar compound, and a low-molecular-weight charged compound—to the same functional group on the particle surface. This was an attempt to enhance charge stability by filling exposed bare spots with low-molecular-weight compounds; however, there is process complexity requiring the precise reaction of the three compounds in a specific order, making it difficult to secure manufacturing yield. In particular, the linear block copolymer structure has a limited arrangement of charge sites relative to the surface area, resulting in clear structural limitations in maximizing the charge density of the particles.

[0005] In conclusion, conventional technologies have limitations, such as the decrease in charge capacity when polymers are introduced to enhance dispersibility, or the difficulty in forming a stable shell structure due to competition for binding sites when composite components are used. Therefore, a new technological approach is required that goes beyond the technical scope of block copolymer-based sequential bonding systems. This approach utilizes a high-density graft structure in which numerous side chains are bonded to a main chain to increase the coverage rate and integrate charging and dispersion functions within a single molecule in a hybrid manner. Furthermore, a technology for forming inter-chain cross-linking networks to prevent the shell from collapsing even under changes in the external environment is essential for process simplification and ensuring the long-term reliability of the particles. Prior art literature

[0006] 1. U.S. Patent No. 7,457,028 2. Japanese Published Patent No. 2013-156381 3. U.S. Patent No. 8,934,165 4. U.S. Patent No. 10,597,541 The problem to be solved

[0007] First, to solve the problems of chemical instability and low surface coverage density associated with conventional linear block copolymer and silane coupling agent-based bonding methods, strong polyvalent covalent bonds based on phosphonic acid and a network cross-linking structure between main chains are formed on the particle surface, thereby providing electrophoretic particles with extreme durability in which the polymer shell does not peel off even under repeated electric field stress and moisture exposure environments.

[0008] Second, to overcome the technical limitations of independently maximizing charge while ensuring particle dispersion stability, an electrophoretic medium is provided that realizes low-voltage driving and high-speed response characteristics by increasing the degree of charge dissociation within a non-polar dispersion medium through the direct introduction of ionic liquid residues into the main chain of the graft polymer.

[0009] Third, to solve the problem of spontaneous aggregation between particles and the resulting ghosting that occurs during high-temperature storage and operation, a fluorine-based and long-chain alkyl hybrid side chain with a number average molecular weight in the range of 500 to 5,000 is introduced to impart a strong critical exclusion volume effect (steric hindrance), thereby providing an electrophoretic medium with long-term reliability.

[0010] Fourth, to solve the charge loss defects caused by the complex manufacturing process and competition for binding site occupancy of conventional three-color sequential coupling systems, an electrophoretic film is provided that physically blocks cross-talk at pixel boundaries by integrating the function into a single graft molecule and binding the chains together with a crosslinking agent.

[0011] Fifth, to solve the problem of the displayed image becoming blurry due to the external leakage of charged ions after power is cut off, a cross-linked polymer shell physically traps ions, providing an electrophoretic display device with excellent bistable performance in which the image remains clear for more than 10 hours without an external power supply.

[0012] Finally, the present invention provides a high-resolution electrophoretic display device that maximizes production yield through a simplified two-step manufacturing process, improves charge stability by more than 30% compared to conventional technology, and dramatically improves reliability under high temperature and electric field stress. means of solving the problem

[0013] An electrophoretic display device according to one embodiment of the present invention comprises: at least one substrate having a common electrode and a driving electrode formed thereon; an electrophoretic film disposed between the substrates; and an electrophoretic medium sealed within the electrophoretic film, wherein the electrophoretic medium comprises a nonpolar dispersion medium and charged electrophoretic particles, and the electrophoretic particles comprise a base particle having a first functional group on its surface, a first compound and a second compound bonded to the base particle, wherein the first compound is a graft polymer copolymerized with a charged monomer unit comprising a phosphonic acid residue forming a multidentate bonding with the first functional group, a side-chain macromonomer unit providing dispersibility, and an ionic liquid residue, and the second compound may be a crosslinking agent that chemically connects the main chains of the first compound to form a shell cross-linking structure over the entire surface of the particle.

[0014] The above base particles are at least one of titanium dioxide (TiO2), titanium nitride (TiN), iron oxide (Fe2O3, Fe3O4), or an organic pigment coated with silica, and the first functional group may be a hydroxyl group (-OH) or a carboxyl group (-COOH) on the surface of the particles.

[0015] The phosphonic acid residue of the first compound is derived from at least one monomer selected from the group consisting of vinylphosphonic acid, 2-methacryloyloxyethyl phosphate, and vinylbenzylphosphonic acid, and forms a POM (M is a metal element) bond with the surface of the base particle, thereby improving shell peeling resistance by more than 10 times compared to conventional silane bonds.

[0016] The side-chain macromonomer unit of the first compound is at least one selected from the group consisting of perfluoropolyether (PFPE), polydimethylsiloxane (PDMS), and long-chain alkyl acrylates having 12 or more carbon atoms, with a number average molecular weight (Mw) in the range of 500 to 5,000, and can provide a critical exclusion volume effect that blocks inter-particle aggregation within the said molecular weight range.

[0017] The charged monomer unit of the first compound comprises at least one ionic liquid residue selected from the group consisting of imidazolium salts, pyridinium salts, and quaternary ammonium salts, and the zeta potential of the particle can be linearly controlled within the range of ±20mV to ±120mV by controlling the density of the ionic liquid residue.

[0018] The second compound above is a low-molecular-weight compound containing two or more epoxy groups, isocyanate groups, or aziridine residues within the molecule, and the network structure formed by the crosslinking agent can physically block the outflow of charged ions to improve the phenomenon of charge loss.

[0019] An electrophoretic particle according to one embodiment of the present invention may comprise: a base particle having a first functional group on its surface, as an electrophoretic particle included in an electrophoretic display device; a graft polymer having a main chain having a phosphonic acid residue bonded to the surface of the base particle, a side chain providing dispersibility, and a charged portion having an ionic liquid residue integrated within a single molecule; and a network cross-linking structure that interweaves the main chains of the graft polymer on the surface.

[0020] An electrophoretic medium according to one embodiment of the present invention may comprise electrophoretic particles; and a nonpolar dispersion medium comprising silicone oil, hydrocarbon oil, or fluorine-based oil.

[0021] In the electrophoretic medium, the electrophoretic particles can have dispersion stability such that the change in the initial average particle size (D50) is maintained within 5% even after being left at 60°C for 1,000 hours due to the cross-linked network structure.

[0022] An electrophoretic film according to one embodiment of the present invention may include a structure in which an electrophoretic medium is filled into a plurality of microcapsules or sealed within a microcell structure formed on a substrate.

[0023] The network cross-linked shell of the electrophoretic particles on the inner side of the outer wall of the microcapsule or microcell prevents electrical adhesion between particles, thereby blocking crosstalk at the pixel boundaries during image switching.

[0024] An electrophoretic display device according to one embodiment of the present invention can have bistable in which the contrast ratio of a displayed image is maintained at 95% or higher of the initial value for more than 10 hours, even when the external power is completely cut off, due to the synergistic effect of the high-density graft structure of the electrophoretic particles and the surface cross-linking network. Effects of the invention

[0025] The electrophoretic particles according to the present invention, the medium containing the same, the film, and the display device provide the following technical effects.

[0026] First, the chemical bonding stability of the particle surface is improved. By forming polyvalent covalent bonds using phosphonic acid derivatives instead of conventional silane coupling agents, the peeling of the polymer shell caused by trace amounts of moisture in the dispersion medium or repeated application of an electric field is suppressed. Test results show that the resistance to shell peeling is strengthened by more than 10 times compared to conventional methods, extending the operating life.

[0027] Second, the control range and stability of the particle's charge amount are improved. By directly introducing ionic liquid residues into the polymer main chain, the degree of charge dissociation in non-polar solvents is increased, allowing for the precise realization of a zeta potential in the range of ±20mV to ±120mV. This enables high electrophoretic mobility even at low voltages, and reduces charge loss phenomena by more than 30% compared to conventional technology.

[0028] Third, dispersion reliability in high-temperature environments is ensured. Graft side chains having a specific molecular weight range (Mw 500~5,000) are arranged at high density to provide a strong steric hindrance effect. Accordingly, irreversible permanent aggregation between particles is prevented even when stored for a long time at high temperatures of 60°C or higher, and the initial particle size distribution is maintained consistently.

[0029] Fourth, the optical visibility and bistability of the display are enhanced. Charge leakage is physically blocked through a surface network cross-linking structure that chemically connects polymer chains. This allows the image to maintain over 95% of the initial contrast ratio for more than 10 hours even after the power is turned off, and effectively suppresses crosstalk and ghosting, which are charge interferences between adjacent pixels.

[0030] Fifth, the efficiency of the manufacturing process is enhanced. By integrating functions into a single graft polymer and employing a simplified process for introducing crosslinking agents, the issue of competition for binding sites between components is resolved, improving product quality uniformity and manufacturing yield. Specific details for implementing the invention

[0031] The present invention is capable of various modifications and may have various embodiments, and specific embodiments are illustrated in the drawings and described in detail. The effects and features of the present invention and the methods for achieving them will become clear by referring to the embodiments described below in detail together with the drawings. However, the present invention is not limited to the embodiments disclosed below but may be implemented in various forms; these embodiments are provided merely to ensure that the disclosure of the present invention is complete and to fully inform those skilled in the art of the scope of the invention, and the present invention is defined only by the scope of the claims.

[0032] In this specification, singular expressions include plural expressions unless the context clearly indicates otherwise.

[0033] In this specification, the terms “comprise” and / or “comprising” specify the presence of the mentioned features, steps, numbers, actions, parts, elements, and / or groups thereof, and do not exclude the presence or addition of one or more other features, steps, numbers, actions, parts, elements, and / or groups thereof.

[0034] In this specification, "at least one of a, b and c" may include a, b, or c alone, or two or more combinations selected from the group consisting of a, b, and c.

[0035] Where various embodiments are described in this specification, each embodiment may be combined unless specifically stated otherwise. In this case, the effects of the present invention may be defined as including effects derived from each embodiment and effects resulting from the organic combination of each embodiment. For example, even if embodiments 1 and 2 are described independently in this specification, unless the context clearly indicates otherwise, embodiments 1 and 2 may be organically combined with each other, and the effects of the present invention may include effects resulting from the combination of embodiments 1 and 2.

[0036] In this specification, a range of numerical values ​​indicated by the term 'to' represents a range of numerical values ​​that includes the values ​​listed before and after the term as the lower and upper limits, respectively. If multiple numerical values ​​are disclosed as the upper and lower limits of an arbitrary numerical range, the range of numerical values ​​disclosed in this specification may be understood as a range of arbitrary numerical values ​​in which any one of the multiple lower limits and any one of the multiple upper limits are respectively the lower limit and upper limit. For example, if the specification states a to b or c to d, it may be understood as stating a to b, a to d, c to d, or c to b.

[0037] In this specification, terms such as “about” or “substantially” refer to a reasonable amount of variation of a term modified so as not to significantly alter the final result. Such terms may be interpreted to include a variation of at least ±5% or at least ±10% to the extent that the variation does not alter or invalidate the meaning of the word.

[0038] I. Composition and Preparation of Electrophoretic Charged Particles

[0039] The present invention completely departs chemically and structurally from the conventional three-color sequential bonding system and block copolymer structure, and is centered on a high-density graft polymer that integrates functions within a single polymer and a surface network crosslinking structure. The technical configuration for the specific realization of the present invention is as follows.

[0040] 1. Base Particle and Surface Activation Composition

[0041] The technical configuration of the present invention is not limited to specific pigments and is applicable to all various inorganic pigments, including iron oxide and titanium dioxide (TiO2), and organic color pigments such as CMY (cyan, magenta, yellow). Since phosphonic acid-based hybrid anchoring technology forms the strongest bond with metal oxide surfaces, an optimized configuration tailored to the surface characteristics of each pigment is implemented as follows.

[0042] (1) White and black

[0043] Titanium dioxide (TiO2) is used as the base particle, which serves as the nucleus of the electrophoretic particle, to achieve a white color. Titanium dioxide (TiO2) is classified into rutile and anatase types depending on its crystal structure, and rutile titanium dioxide, which has a higher refractive index, is advantageous in terms of scattering efficiency. In addition, inorganic pigments such as zinc oxide (ZnO), barium sulfate (BaSO4), and zirconium dioxide (ZrO2) are used as core materials. The average particle size is maintained in the range of 150 nm to 500 nm, and hydroxyl groups (-OH) or carboxyl groups (-COOH) capable of reacting with phosphonic acid residues exist on the surface as primary functional groups. In the case of organic pigments, surface energy is increased through plasma treatment or ozone treatment, and oxygen functional groups are forcibly introduced to maximize bonding strength.

[0044] To achieve black color, particles with high optical density and excellent electrical stability, such as iron oxide (triiron dioxide (Hematite, Fe2O3) or triiron oxide (Fe3O4, Magnetite)), copper chromite, and titanium nitride (TiN), are used as cores. Although iron oxide can possess magnetic properties, in this invention it primarily functions as a light absorber. For long-term stability within an electro-optical medium, the surface of the iron oxide has a composite structure coated with a polymer or inorganic material. Iron oxide is suitable for achieving a perfect black color and forms a very robust shell through metal-oxygen-phosphorus (MOP) bonding with the phosphonic acid main chain of this invention. To offset the high specific gravity of the iron oxide, buoyancy is precisely controlled by adjusting the length of the grafted side chains.

[0045] In addition, available materials are as follows.

[0046] Carbon Black: It has a fine particle size and a high absorption coefficient. It includes channel black, furnace black, and lamp black. The bonding strength with the polymer shell varies depending on the density of functional groups (carboxyl groups, hydroxyl groups, etc.) on the surface.

[0047] Metal oxide-based black pigments: Copper chromite spinel, iron-manganese complex oxide, etc., are used. They have higher chemical stability and lower conductivity than carbon black, making them advantageous for reducing electrical interference.

[0048] Organic black pigments: Synthetic organic pigments such as aniline black can be used. They have a lower specific gravity compared to inorganic pigments, which is advantageous for maintaining dispersion.

[0049] (2) Types of color particles and core materials

[0050] A full-color system is constructed using natural or synthetic organic pigments. Since organic pigments have a low surface hydroxyl group density, the present invention enables hybrid anchoring by performing a preliminary 'metal oxide thin film encapsulation' step.

[0051] Cyan particles: Copper phthalocyanine-based pigments are used.

[0052] Magenta particles: Quinacridone or diketopyrrolopyrrole (DPP)-based pigments are used.

[0053] Yellow particles: Isoindoline or diarylide-based pigments are used.

[0054] Surface pretreatment for color particles: The surface of the above organic pigments is coated with a thin film of silica (SiO2) or alumina (Al2O3) to a thickness of 1 to 10 nm. This inorganic coating layer provides abundant hydroxyl (-OH) sites where the vinyl phosphonic acid main chain, which is the core of the present invention, can form polydentate bonds.

[0055] (3) Optimized charging and dispersion design for each pigment

[0056] The polymer composition is differentiated so that each color particle behaves independently within a single medium without interfering with one another.

[0057] White / Black Particles: Due to their large particle size and specific gravity, the density of graft side chains (second monomer units) is maximized, providing strong steric hindrance repulsion.

[0058] Color particles (CMY): By utilizing the low specific gravity characteristics of organic pigments and setting a high concentration of ionic liquid residues (third monomer units) within the main chain, the electrophoretic mobility is designed to be more than twice as high as that of white / black. Through this, high-resolution color separation control is realized, in which a specific color emerges to the surface first depending on the magnitude of the voltage.

[0059] The base particles are inorganic pigments selected from titanium dioxide, iron oxide, copper chromite, and titanium nitride depending on the color to be displayed, or organic pigments selected from copper phthalocyanine, quinacridone, and isoindoline with their surfaces coated with silica or alumina.

[0060] The common first functional group (hydroxyl group) of all these pigment particles reacts with the phosphonic acid residue of the graft polymer, which is the first compound of the present invention, to be chemically fixed. In particular, the surface potential and surface energy values ​​of each pigment are controlled independently to prevent electrical entanglement between particles. For example, black iron oxide particles increase the density of the main chain crosslink (second compound) to block charge leakage, and white titanium dioxide particles increase the specific gravity of the fluorine-based side chain to prevent a decrease in reflectance.

[0061] Consequently, the present invention provides a multicolor electrophoretic medium that completely resolves the problems of charge misalignment and aggregation between multiple particles, which existing E-ink patents have failed to solve, by stably realizing a deep black state based on iron oxide and a vivid color state based on CMY organic pigments within the same hybrid network shell.

[0062] 2. First Compound: Functionally Integrated High-Density Graft Polymer

[0063] Instead of conventional linear block copolymers, a graft structure composed of a backbone and side chains is adopted. This offers a structural advantage that allows for the placement of dispersion segments with a much higher density relative to the surface area occupied by the particles.

[0064] a. Binding part (first monomer unit)

[0065] Vinylphosphonic acid or 2-methacryloyloxyethyl phosphate is copolymerized as part of the main chain. Phosphonic acid residues form much stronger multidentate bonding with metal oxide surfaces compared to silane coupling agents, preventing chemical desorption of the shell through PO-Ti type phosphonate bonds.

[0066] The bonding portion (first monomer unit) responsible for chemical bonding with the particle surface in the main chain of the graft copolymer, which is the first compound of the present invention, is composed of various functional compounds capable of forming polylocerate bonds by completely replacing conventional silane coupling agents. In addition to vinyl phosphonic acid and 2-methacryloyloxyethyl phosphate, compounds applicable to the present invention are as follows.

[0067] (1) Phosphonic acid and phosphinic acid derivatives

[0068] Phosphonic acid groups have the best polydentate bonding characteristics, in which two or more oxygen atoms form covalent bonds with hydroxyl groups (-OH) on the surface of metal oxides.

[0069] Vinylbenzylphosphonic acid: Contains a benzene ring to increase the stiffness of the main chain and provides stability through an electron-conjugated structure upon charge dissociation.

[0070] Allylphosphonic acid: The polymerization rate is slow, allowing for precise control of the grafting density on the particle surface.

[0071] Methacrylamidoethylphosphonic acid: Provides hydrogen bonding assistance by including amide bonds and maximizes the reactivity of phosphonic acid residues.

[0072] Bis(2-methacryloyloxyethyl) phosphinic acid: It has two polymerizable groups within one molecule and plays a role in simultaneously increasing the crosslinking density of the shell.

[0073] (2) Phosphate series and phosphate ester derivatives

[0074] Phosphate ester structures have a very high affinity for metal ions, and derivatives with various chain lengths can be applied.

[0075] Monoacryloyloxyethyl phosphate: Due to low steric hindrance, it can penetrate into fine pores on the particle surface and form bonds.

[0076] Acid Phosphoxy Polyoxyethylene Glycol Methacrylate: A structure in which a phosphate group is bonded to the end of a long polyethylene glycol chain, providing initial dispersion force simultaneously with bonding.

[0077] Vinyl benzyl phosphate: The combination of an aromatic ring and a phosphate ester results in excellent compatibility with organic pigment coating layers.

[0078] (3) Catechol-based anchoring monomer

[0079] With a structure based on the principles of mussel adhesive proteins, it forms strong, irreversible bonds to both metal oxide and organic pigment surfaces.

[0080] Dopamine methacrylamide (DMA): The two hydroxyl groups of the catechol residue form chelate bonds with metal ions, having a binding energy tens of times higher than that of silane bonds.

[0081] 3,4-Dihydroxybenzyl methacrylate: Maintains a stable shell structure in both acidic and basic environments through a direct condensation reaction with the pigment surface.

[0082] 4-Vinylcatechol: The catechol group is directly bonded to the carbon skeleton of the main chain, which can increase the coating density to the extreme.

[0083] ((4) Polyfunctional Carboxylic Acid and Sulfonic Acid Derivatives

[0084] Phosphonic acid acts as an auxiliary or independent anchor on the surface of specific metal (Al, Mg, etc.) pigments.

[0085] Itaconic acid: Possesses two carboxyl groups within a single monomer, inducing polydentate bonding with metal surfaces.

[0086] 2-Acrylamido-2-methylpropanesulfonic acid (AMPS): Forms electrostatic and covalent bonds with metal oxides simultaneously through strong acidic functional groups.

[0087] Vinylsulfonic acid: Due to its very small molecular size, it can be used in combination for 'post-capping' purposes, which completely fill the binding sites on the particle surface.

[0088] (5) Acetoacetoxy and other coordination monomers

[0089] 2-(acetoacetoxy)ethyl methacrylate (AAEM): Forms a stable chelate ring in the form of a six-membered ring with metal ions to fix the polymer shell.

[0090] Vinylphosphonic acid dimethyl ester: Can be used in the form of a precursor that generates surface bonding strength through acid hydrolysis after polymerization.

[0091] The compounds listed above are used alone or mixed in two or more forms to constitute the first monomer unit. In particular, when phosphonic acid-based monomers and catechol-based monomers are used in combination, they mutually occupy different reaction sites on the surface of metal oxides, thereby securing a level of bonding density and chemical durability that cannot be achieved with conventional silane coupling agents. This is a key technical means of suppressing fluctuations in zeta potential to within 5% even under repeated electric field stress.

[0092] B. Dispersion part (second monomer unit)

[0093] Perfluoropolyether (PFPE) or polydimethylsiloxane (PDMS) macromonomers with a number average molecular weight of 500 to 5,000 are used as side chains grafted onto the main chain. This forms strong steric hindrance within the dispersion medium, such as silicone oil or fluorine-based oil, thereby blocking aggregation between particles. In particular, universal compatibility in various non-polar media is secured through a hybrid side chain composition in which PFPE and PDMS are mixed.

[0094] The second monomer unit forming the side chain of the graft copolymer of the present invention includes a wide group of compounds in addition to PFPE and PDMS to control compatibility with the dispersion medium and maximize the steric hindrance effect. First, long-chain alkyl monomers such as stearyl or behenyl (meth)acrylates having 12 to 22 carbon atoms enhance dispersibility in hydrocarbon oils, while branched monomers such as 2-ethylhexyl or isodecyl acrylates increase the flexibility of the polymer shell and the degree of swelling in the solvent to maximize steric hindrance. Polyisobutylene (PIB) macromonomers or hydrogenated polybutadiene derivatives physically and completely block electrostatic aggregation between particles through excellent affinity with non-polar media, and fluorinated alkyl monomers of various chain lengths such as perfluorooctyl or perfluorodecyl acrylates play a role in drastically lowering the surface energy of the particles. In addition, poly(12-hydroxystearic acid) derivatives or polypropylene glycol (PPG) mono(meth)acrylates precisely control the chemical stability and steric occupancy volume of the dispersion chain, while long-chain vinyl esters or vinyl ether compounds simultaneously reinforce the hydrophobicity and physical durability of the shell. Furthermore, reactive polyhedral silsesquioxane (POSS) derivative acrylates form large-volume organic-inorganic hybrid nanostructures on the particle surface, and macromonomers containing reactive functional groups derived from oleic acid or linoleic acid maximize physicochemical affinity with low-dielectric media, providing unchanging dispersion retention even under temperature changes and repeated electric field environments.

[0095] C. Charged portion (third monomer unit)

[0096] An ionic liquid residue, such as 1-vinyl-3-butylimidazolium bis(trifluoromethanesulfonyl)imide, is introduced into the main chain. This results in a significantly higher degree of charge dissociation in non-polar solvents compared to conventional simple polarizers, thereby improving the electrophoretic mobility of particles by more than 30% even at low voltages and precisely achieving the target zeta potential within the range of ±20mV to ±120mV.

[0097] The third monomer unit forming the charged portion of the present invention includes various ionic compounds capable of maximizing charge separation ability in a non-polar medium, in addition to the aforementioned imidazolium-based ionic liquid. As for the cationic component, not only imidazolium derivatives having other substituents such as 1-vinyl-3-methylimidazolium and 1-(4-vinylbenzyl)-3-methylimidazolium, but also pyridinium-based monomers such as 4-vinylpyridinium, 1-methyl-4-vinylpyridinium, and 2-vinylpyridinium, and ammonium-based monomers such as 2-(methacryloyloxy)ethyltrimethylammonium and quaternized derivatives of dimethylaminoethyl (meth)acrylate can be widely adopted. In addition, phosphonium derivatives such as tri-n-butyl(vinylbenzyl)phosphonium or tetrabutylphosphonium methacrylate, and sulfonium ionic monomers such as dimethyl(vinylbenzyl)sulfonium are introduced to precisely control the polarity and amount of charge. As for the anion counter-ions that bind to these cations, in addition to bis(trifluoromethanesulfonyl)imide (TFSI), bis(fluorosulfonyl)imide (FSI), hexafluorophosphate (PF6), tetrafluoroborate (BF4), trifluoromethanesulfonate (Triflate), dicyanamide, and heptafluorobutyrate are used alone or in combination to optimize the degree of charge dissociation in a low dielectric medium. These various ionic residues form dense charge trap sites within the polymer main chain and serve as a key means to realize low-voltage driving and high-speed response characteristics by linearly controlling the particle's zeta potential to a target range of ±20mV to ±120mV.

[0098] 3. Second Compound: Shell Cross-linking

[0099] While conventional patents were limited to a 'capping' method that fills empty spaces with low-molecular-weight compounds, the present invention introduces a second compound (crosslinking agent) that chemically links the main chains of the first compound.

[0100] A multifunctional crosslinking agent, such as polyethylene glycol diglycidyl ether or hexamethylene diisocyanate, is added to form a physical and chemical mesh network between the polymers bonded to the particle surface. This crosslinking structure prevents the entanglement of polymer chains and loss of charge that occurs during collisions between particles or repeated application of an electric field, and is a key technological means to increase the mechanical strength of the shell and reduce ghosting problems in display devices.

[0101] The surface crosslinking agent, which is the second compound imparting physical rigidity and electrostatic stability to the shell structure of the present invention, includes various polyfunctional compounds depending on the reactive functional groups of the main chain. As epoxy-based crosslinking agents, in addition to the aforementioned diglycidyl ether derivatives, triglycidyl isocyanurate (TGIC), sorbitol polyglycidyl ether, pentaerythritol polyglycidyl ether, trimethylolpropane triglycidyl ether, etc. are used, and as isocyanate-based agents, aliphatic and aromatic polyfunctional derivatives such as toluene diisocyanate (TDI), isophorone diisocyanate (IPDI), xylylene diisocyanate, and polymerized MDI can be applied. In addition, polyfunctional aziridine compounds such as trimethylolpropane tris(2-methyl-1-aziridinepropionate) or water-dispersible polycarbodiimide derivatives induce rapid crosslinking network formation even at room temperature. For shell fixation through radical copolymerization, polyfunctional vinyl or (meth)acrylic monomers such as divinylbenzene (DVB), ethylene glycol dimethacrylate (EGDMA), trimethylolpropane triacrylate (TMPTA), and pentaerythritol tetraacrylate may be adopted. Furthermore, metal chelate crosslinkers such as aluminum acetylacetonate, zirconium tetraacetylacetonate, and titanium tetraisopropoxide enhance the chemical resilience of the shell through coordination bonding, while epoxysilane or aminosilane crosslinkers such as 3-glycidyloxypropyl trimethoxysilane form an organic-inorganic hybrid network structure, thereby preventing mechanical failure of the shell and exhibiting a remarkable effect of maximizing bistable by physically trapping the movement of charged ions when the power is cut off.

[0102] 4. Simplification and Optimization of Manufacturing Processes

[0103] The present invention simplifies the conventional complex three-step sequential process of [charger bonding → dispersant bonding → non-polar agent bonding] into two steps of [graft polymer bonding → surface crosslinking].

[0104] Polymer Synthesis: A graft copolymer in which the bonding, dispersion, and charging regions are integrated is pre-synthesized through radical polymerization.

[0105] Hybrid anchoring: Reacting a synthesized polymer with base particles to induce strong polydentate bonding based on phosphonic acid.

[0106] Shell crosslinking: A crosslinking agent is introduced into a reactor to fix the shells formed on the particle surface into a network structure.

[0107] This process resolves the problem of each compound competing for binding sites, thereby increasing quality uniformity and maximizing manufacturing yield.

[0108] II. Characteristics of Electrophoretic Particles

[0109] The present invention provides a high-performance surface modification technology that fundamentally alters the conventional chemical composition to maximize the dispersion stability and electrostatic reliability of electrophoretic particles. The specific technical configuration for implementing the present invention is as follows. To overcome the chemical instability associated with the single bond (-Si-O-) method of silane coupling agents adopted in conventional technology, the present invention uses a vinylphosphonic acid derivative as a core bonding unit.

[0110] Phosphonic acid residues react with metal ions (Ti, Fe, Al, etc.) on the surface of metal oxide pigments to form multidentate bonding in which one or more oxygen atoms participate in the bonding. This results in significantly higher bonding energy compared to silane-based systems and exhibits excellent resistance to hydrolysis caused by trace amounts of moisture, particularly in non-polar dispersion media. This phosphonate bonding structure physically prevents the polymer shell from peeling off from the particle surface even when the particles undergo millions of repeated movements under an electric field, and prevents the exposure of the particle core, thereby maintaining the linearity of the charge behavior for a long period.

[0111] 2. High-density graft polymer topology (Graft Topology)

[0112] The first compound of the present invention excludes conventional linear block copolymers and has a graft copolymer structure in which high-density side chains are densely bonded to a backbone.

[0113] This graft polymer takes the form in which the main chain is arranged horizontally along the particle surface, while the side chains responsible for dispersibility extend vertically. This topology can increase the density of dispersed chains per unit area of ​​the particle surface by more than three times compared to a linear block structure. This enables uniform control of the thickness of the polymer shell formed on the particle surface and resolves the steric hindrance problem that occurs during macromolecular bonding, thereby raising the coverage rate to over 99%. Consequently, it completely eliminates 'bare spots,' which are spaces where van der Waals forces act between particle cores, thereby fundamentally suppressing spontaneous aggregation between particles.

[0114] 3. Charge Control Using Ionic Liquid Residues (Ionic Liquid Charging g)

[0115] The present invention directly introduces ionic liquid functional groups into the polymer main chain to realize low-voltage driving and high-speed response characteristics.

[0116] The charged monomer used contains 1-vinyl-3-alkylimidazolium or vinylpyridinium residues, and forms a counterion with a hydrophobic anion such as bis(trifluoromethanesulfonyl)imide (TFSI). The ionic liquid residue maintains high charge separation ability even in non-polar media and possesses the characteristic of widely dispersed (delocalized) charge within the molecule. Through this, a highly stable electric double layer is formed on the particle surface, allowing the zeta potential to be precisely and linearly controlled from ±20mV to ±120mV. This solves the problem of insufficient charge in conventional simple polarizers and provides a significant effect of improving the electrophoretic mobility of particles by more than 30% compared to conventional methods when an electric field is applied.

[0117] 4. Triple Hybrid Dispersion Segment (Hybrid Dispersion)

[0118] The present invention applies a hybrid dispersion system in which three heterogeneous segments are combined in a second monomer unit (side chain) to ensure compatibility in various non-polar dispersion media.

[0119] Silicone-based segment: Polydimethylsiloxane (PDMS) acrylate is introduced to induce stable swelling in a silicone oil medium.

[0120] Fluorine-based segment: Perfluoropolyether (PFPE) macromonomers are introduced to ensure dispersibility in fluorine-based solvents and drastically lower the surface energy of the particles.

[0121] Aliphatic long-chain segment: A stearyl or behenyl acrylate having 12 to 22 carbon atoms is introduced to maximize the exclusion volume effect in hydrocarbon oils.

[0122] This triple hybrid configuration ensures that polymer chains maintain an unfolded structure without shrinking within the solvent, even when the type of medium is changed or mixed. This generates strong steric hindrance repulsion during particle collisions, preventing permanent aggregation, eliminating ghosting in display devices, and improving image contrast ratio.

[0123] 5. Formation of surface network cross-linking structure

[0124] The second compound of the present invention acts as a shell cross-linker that chemically links the bonded graft polymers. A polyfunctional compound, such as a diglycidyl ether or a diisocyanate derivative, reacts with the polymer main chains on the particle surface to form a rigid network structure that envelops the entire particle. This network structure prevents physical deformation of the shell due to external pressure or temperature changes, and physically traps the outflow of charged ions, thereby providing excellent bistable that maintains the image for a long time even when the power is turned off.

[0125] III. Preparation of Microcapsules

[0126] Microcapsules containing electrophoretic particles according to the present invention are manufactured by a complex coacervation method to optimize the behavior of high-performance particles modified with hybrid bonding and surface crosslinking networks and to protect them from the external environment.

[0127] First, the electrophoretic fluid constituting the internal phase of the microcapsule is composed mainly of an aliphatic hydrocarbon solvent such as Isopar (Isopar G, Isopar M) or silicone oil, which has low dielectric constant and viscosity. Within this fluid, white titanium dioxide particles, black iron oxide (triiron dioxide (Hematite, Fe2O3) or triiron oxide (Fe3O4, Magnetite)) particles manufactured by the core technology of the present invention, and colored organic pigment particles such as cyan, magenta, and yellow are mixed and dispersed. At this time, the particles are equipped with a high-density graft main chain and a surface network cross-linking structure, thereby maintaining a state in which aggregation between particles is suppressed. To preserve the charge stability of the particles, a charge control agent (CCA) of the oleic acid or succinimide series, such as Solsperse™, Lubrizol™, sodium sulfosuccinate, and cobalt naphthenate, is dissolved to form a stable charge system.

[0128] The outer wall of the microcapsule uses a mixture of gelatin and gum arabic, which are hydrophilic polymers, to maximize interfacial adhesion with the binder used in subsequent processes, or, if heat resistance is required, polyurethane or polyurea-based synthetic polymers are adopted. The manufacturing process begins with an emulsification step in which a prepared electrophoretic fluid is introduced into an aqueous gelatin solution dissolved in water and dispersed into fine droplets using a high-shear stirrer. At this time, the stirring speed and the concentration of the surfactant are precisely controlled to form capsules with an average particle size in the range of 20 micrometers to 60 micrometers.

[0129] Once emulsification is complete, a gum arabic solution is added, and while maintaining the system temperature at 40 to 50 degrees, acetic acid or the like is added dropwise to gradually lower the pH to a range of 4.0 to 4.8. As the pH changes, a strong electrostatic attraction occurs between the positively charged gelatin and the negatively charged gum arabic, and they are selectively deposited on the surface of the electrophoretic fluid droplets to form an initial wall film. Subsequently, the temperature is rapidly cooled to below 10 degrees to fix the gelatin structure, and then a crosslinking agent such as glutaraldehyde is added to induce chemical covalent bonding of the outer wall, thereby completing a thermally and mechanically stable solid wall film.

[0130] To further reinforce the mechanical strength of the capsule, a secondary curing process is performed by adding CMC (Carboxymethylcellulose sodium salt) and raising the temperature again to above 40 degrees. Through this process, CMC is bonded to the surface of the wall film, forming a dense structure that is not damaged by external pressure or shear force during binder mixing. Finally, the capsule is recovered through centrifugation and filtration, residual reactants are removed through a washing step, and a microcapsule slurry with a uniform size distribution is obtained through particle size sorting using a standard mesh.

[0131] The completed microcapsule maintains a thin insulating outer wall with a thickness of 1 to 3 micrometers, transmitting an external electric field to the internal particles without loss. In particular, the graft particles with the ionic liquid residues introduced in the present invention exhibit a fast response speed in the millisecond (ms) range even at low voltages of plus or minus 15V or less, combined with the low viscosity characteristics of the internal fluid, and clearly realize high-resolution multicolor images by forming a clear threshold voltage through the optimization of the dielectric properties of the outer wall.

[0132] IV. Preparation of Electrophoresis Media and Films

[0133] The manufacturing process of an electrophoretic medium, film, and display device comprising charged particle microcapsules according to the present invention is carried out as follows to ensure optical uniformity and mechanical reliability while maintaining the inherent charge characteristics of the particles.

[0134] The electrophoretic medium is defined as a mixture of microcapsules prepared by the aforementioned composite coacervation method and a polymer binder for immobilizing them on a substrate. The film manufacturing process is based on a coating technology capable of large-area application.

[0135] First, a microcapsule slurry with a solid content of 40% is mixed with a water-dispersible polyurethane (PUD) nanoparticle binder. The binder penetrates into the gaps between the microcapsules, firmly adhering the capsules to the substrate while simultaneously forming a three-dimensional point contact network. At this time, a fluorine-based wetting agent or a small amount of organic solvent is added to improve coating properties, and the coating slurry is prepared by gently stirring with a low-speed impeller of 100 rpm or less to prevent bubble formation.

[0136] The prepared slurry is applied onto an ITO-PET transparent electrode film having a surface resistance of 100 Ω / sq or less using a comma coater or a slot-die coater. The coating thickness is precisely controlled within the range of 20 micrometers to 35 micrometers so that microcapsules can be arranged in a monolayer after drying. The coated film is cured by evaporating moisture in a hot air dryer at approximately 70°C. A polyurethane-based lamination adhesive film is placed on the dried display layer, and after undergoing a heat-press lamination process, a back-side protective PET film is laminated to complete the final electrophoretic film.

[0137] V. Assembly and Manufacture of Electrophoretic Display Devices (EPD)

[0138] The process of completing the final display device by integrating the manufactured electrophoretic film with a backplane on which a driving circuit is formed requires a high degree of precision.

[0139] First, the electrophoretic film is precisely cut to match the designed display specifications. For the back substrate, a thin-film transistor (TFT) array substrate capable of independently driving each pixel or a segment electrode substrate for displaying specific characters is prepared. Before lamination, the surface energy of the back substrate is optimized by treating it with oxygen plasma or UV-ozone to enhance insulation between pixels and prevent lateral charge bleeding.

[0140] Second, the protective sheet of the cut film is removed, and the exposed adhesive layer is aligned to face the electrode surface of the back substrate. Then, lamination is performed using a vacuum laminator or a heating roller at a temperature of about 60 to 100 degrees and under constant pressure. At this stage, the microcapsules of the present invention maintain structural integrity without being damaged during the compression process thanks to the outer wall reinforced by a secondary curing reaction.

[0141] Third, the upper common electrode (ITO) of the film and the driving terminal of the rear substrate are connected using an anisotropic conductive film (ACF), and a flexible circuit board (FPC) equipped with a driving IC is bonded. Finally, the display device is finally encapsulated by performing an edge sealing process in which a high-barrier epoxy resin or UV-curable sealant is applied to prevent moisture or impurities from penetrating through the side edges of the substrate.

[0142] VI. electrophoretic display device Operating method

[0143] The driving method of the electrophoretic display device according to the present invention is carried out in the following steps to maximize the electrical characteristics of the high-density graft polymer and the surface network crosslinking structure formed on the particle surface, thereby realizing a high-contrast image without afterimage even at low voltage and maintaining bistable for a long time.

[0144] 1. Fundamental Principles of Particle Behavior Under the Application of an Electric Field

[0145] The basic principle of operation is that charged electrophoretic particles move within a dispersion medium by receiving a Coulomb force within an electric field formed by applying a voltage between an upper transparent electrode and a lower driving electrode. The particles of the present invention possess a strong surface charge due to ionic liquid residues, such as imidazolium or quaternary ammonium, introduced into the main chain, and thanks to the high degree of charge dissociation in a non-polar medium, they respond sensitively even at low electric field strengths and move rapidly toward the electrode.

[0146] 2. Initialization Phase (Reset Phase)

[0147] Before displaying a new image, an initialization process is performed to remove the history of the previous image and to uniformly align the charge state of the particles. A high-frequency alternating voltage (AC) with a constant period or pulses of the maximum driving voltage are applied repeatedly to all pixel electrodes. Through this process, particles that were fixed to specific electrodes inside the microcapsules become able to flow freely, which serves as the basis for preventing ghosting and improving the color purity of the next image.

[0148] 3. Image Writing Phase

[0149] Based on the target image data, a direct current (DC) voltage of a specific polarity and magnitude is applied to each pixel electrode.

[0150] White / Black Display: To move positively charged particles toward the upper observer, a positive (+) voltage is applied to the lower electrode and a negative (-) voltage to the upper electrode, or vice versa, to form light and dark.

[0151] Gray-scale and color display: A pulse width modulation (PWM) method is used to adjust the amplitude of the voltage or to precisely control the pulse width. Since the particle of the present invention has a zeta potential that is linearly adjusted from ±20mV to ±120mV, the reach distance of the particle can be precisely controlled in proportion to the total amount of applied voltage (Impulse), thereby enabling smooth gray-scale expression.

[0152] 4. Bistability Maintenance Phase

[0153] After the image is written, the power is completely turned off. The surface network cross-linking structure (a network formed by the second compound), which is the core of the present invention, physically traps charged ions on the particle surface from escaping into the solvent even when the electric field is gone. In addition, the strong steric hindrance repulsion provided by the high-density graft structure suppresses particles from settling due to gravity or randomly diffusing due to thermal Brownian motion. Through this, ultra-low power operation is realized in which the displayed image maintains the initial contrast ratio for more than 10 hours without a separate energy supply.

[0154] 5. Afterimage suppression and crosstalk prevention mechanism

[0155] When particles reach the electrode surface during operation, the shell cross-linked network prevents electrical adhesion between the particles. In conventional block copolymers, chains would become entangled or delaminate under repeated electric field stress, causing crosstalk where charges spread sideways; however, the cross-linked network structure of the present invention maintains the shape of the particles and blocks the lateral movement of charges. Consequently, characters with clear boundaries and high-resolution images are rendered without afterimages, and a constant response speed is maintained without changes in driving voltage even during repeated operation.

[0156] When a driving voltage of plus or minus 15V or less is applied to the completed electrophoretic display device, the graft polymer particles inside the capsule rapidly move according to the direction of the electric field. Thanks to the ionic liquid residue and surface cross-linking network of the present invention, the degree of ionic dissociation of the particles within the medium is maximized, exhibiting a high contrast ratio (CR) of 15:1 or higher even at low voltages.

[0157] In particular, the network cross-linking structure that interweaves the polymer main chains physically blocks the crosstalk phenomenon, where charges spread sideways when particles reach the electrode surface, thereby dramatically improving character visibility. Furthermore, since the cross-linked shell structure stably maintains the charged state even when the external power is turned off, it provides excellent memory characteristics and bistable, ensuring that no afterimage remains for more than 10 hours after image switching. This is the result of overcoming the physical delamination problem and charge loss defects associated with the conventional block copolymer method.

[0158] VII. Preparation Example of Electrophoretic Particles

[0159] [Preparation Example 1] Preparation of white particles

[0160] A first type of white electrophoretic particle having a high-density graft polymer and a surface network crosslinking structure was prepared by the following process.

[0161] 1. Synthesis of Functionally Integrated Graft Copolymer (First Compound)

[0162] Before bonding to the particle surface, a graft copolymer integrating dispersion, charging, and bonding functions within a single molecule was synthesized in advance.

[0163] First, 300g of methyl ethyl ketone (MEK) was added to a reactor as a solvent. To this, 5g of vinylphosphonic acid as a binding monomer, 10g of 1-vinyl-3-butylimidazolium bis(trifluoromethanesulfonyl)imide as a charging monomer, and 50g of perfluoropolyether (PFPE) acrylate (number average molecular weight 2,000) and 30g of polydimethylsiloxane (PDMS) acrylate (number average molecular weight 5,000) as dispersion macromonomers were mixed and added. Additionally, 5g of glycidyl methacrylate was added to provide functional groups for a subsequent crosslinking reaction.

[0164] After adding 0.6 g of azobisisobutyronitrile (AIBN), a radical polymerization initiator, the inside of the reactor was sufficiently replaced with a nitrogen stream to remove oxygen. Subsequently, the polymerization reaction was carried out for 12 hours while maintaining a temperature of 75°C. After the reaction was completed, the solution was reprecipitated by adding it dropwise to an excess amount of hexane, thereby removing unreacted monomers and obtaining a graft copolymer with a weight average molecular weight (Mw) of approximately 45,000.

[0165] 2. Surface hybrid anchoring process of white particles

[0166] A process was performed to chemically and firmly fix the synthesized graft polymer to the surface of the pigment particles.

[0167] 100 g of rutile-type titanium dioxide (TiO2, average particle size 250 nm) as base particles was added to 500 g of anhydrous toluene. To ensure complete dispersion of the particles, a dispersion treatment was performed for 1 hour using a high-power ultrasonic disperser. 15 g of the above-synthesized graft copolymer was added to the dispersion and stirred.

[0168] The temperature of the reaction system was raised to 110°C and the reflux reaction was continued for 18 hours. During this process, phosphonic acid residues included in the main chain of the copolymer underwent a direct condensation reaction with hydroxyl groups (-OH) on the surface of TiO2, thereby forming polyvalent covalent bonds of the PO-Ti type, which are more stable than silane bonds, at a high density on the particle surface.

[0169] 3. Process for forming a surface cross-linked network (second compound)

[0170] A process was carried out to chemically link the bonded polymer chains to maximize the mechanical strength of the shell and fix the charge state.

[0171] After adjusting the temperature of the particle suspension, in which the anchoring reaction was completed, to 80°C, 2g of polyethylene glycol diglycidyl ether was added as the second compound, a crosslinking agent. A small amount of trimethylamine was added as a reaction catalyst, and the reaction was carried out with additional stirring for 4 hours. Through this, the crosslinking agent molecules sterically connected the epoxy groups within the graft main chain, thereby completing an elastic shell-crosslinking structure that covered the entire surface of the particle.

[0172] 4. Purification and Final Mediation Process

[0173] A purification process was performed to increase the purity of the manufactured particles and to transition them into the final dispersion medium.

[0174] The reaction-completed suspension was centrifuged at 10,000 rpm for 30 minutes to separate the unbound residual polymer and crosslinking agent. Subsequently, the washing process, including centrifugation and redispersion using Isopar-G solvent, was repeated three times to completely remove impurities. The washed particles were dried in a vacuum oven at 60°C for 12 hours to obtain the final white electrophoretic particle powder.

[0175] Thermogravimetric analysis (TGA) of the manufactured white particles confirmed that a rigid polymer shell of approximately 8.2 wt% was formed on the pigment surface. Zeta potential measurements showed a stable strong negative charge of -98 mV in a non-polar medium. In particular, no peeling of the shell or degradation of the charge was observed even after more than 1 million cycles of repeated electric field application tests, and excellent bistability was demonstrated by maintaining the initial image for more than 12 hours even after power was cut off. This implies that a level of physicochemical reliability unattainable with conventional block copolymer and silane bonding technologies has been secured.

[0176] [Preparation Example 2] Preparation of black particles

[0177] A second type of black electrophoretic particle, equipped with a high-density graft polymer and a surface network crosslinking structure, was manufactured using the manufactured iron oxide (Fe2O3) particles as a base through the following process.

[0178] 1. Synthesis of a Functionally Integrated Positively Charged Graft Copolymer (First Compound)

[0179] Considering the dispersibility of iron oxide particles, which have electrical properties opposite to those of white particles and high specific gravity, a graft copolymer incorporating positively charged ionic liquid residues and long-chain dispersed segments was synthesized in advance.

[0180] First, 300g of methyl ethyl ketone (MEK) was added to a reactor as a solvent. To this, 5g of vinylphosphonic acid as a binding monomer, 15g of 2-(methacryloyloxy)ethyltrimethylammonium bis(trifluoromethanesulfonyl)imide as a charged monomer for imparting a strong positive charge, and 40g of perfluoropolyether (PFPE) acrylate (Mw 2,000) and 40g of C18 stearyl acrylate as dispersion macromonomers were mixed and added. Additionally, 5g of glycidyl methacrylate was added to provide a functional group for shell crosslinking.

[0181] 0.6 g of AIBN, a radical polymerization initiator, was added, and polymerization was carried out at 75°C for 12 hours after nitrogen substitution. After the reaction was completed, unreacted monomers were removed by reprecipitation in methanol, thereby obtaining a positively charged graft copolymer with a weight average molecular weight (Mw) of approximately 52,000.

[0182] 2. Surface Hybrid Anchoring Process of Black Iron Oxide Particles

[0183] A process was performed to chemically bond the synthesized graft polymer to the surface of the iron oxide pigment.

[0184] 100g of black iron oxide particles (Fe2O3, average particle size 250nm) directly synthesized as base particles were added to 500g of anhydrous toluene. To prevent sedimentation due to the high specific gravity of iron oxide and to induce a uniform reaction, a high-power ultrasonic disperser was used to perform a vigorous dispersion treatment for 1.5 hours. 20g of the above-synthesized positively charged graft copolymer was added to this dispersion.

[0185] The temperature of the reaction system was raised to 110°C and the reflux reaction was continued for 20 hours. During this process, the phosphonic acid residues of the copolymer reacted directly with iron ions and hydroxyl groups (-OH) on the surface of the iron oxide to form a polyvalent covalent bond of the Fe-OP type, thereby completing a hybrid anchoring layer with a bond energy significantly higher than that of silane bonds.

[0186] 3. Process for forming a surface cross-linked network (second compound)

[0187] A crosslinking process was performed to block the high surface energy of iron oxide particles and increase the physical resilience of the shell.

[0188] With the temperature of the black particle suspension, after the anchoring reaction was completed, maintained at 80°C, 1.5 g of hexamethylene diisocyanate was added as the second compound, a crosslinking agent. A small amount of dibutyltin dilaurate was added as a reaction catalyst, and the mixture was stirred for 5 hours. Through this, the crosslinking agent molecules chemically bonded between the graft main chains, forming a dense shell-crosslinking structure that completely covered the particle surface.

[0189] 4. Purification and Final Mediation Process

[0190] The reaction-completed suspension was centrifuged at 12,000 rpm for 30 minutes to remove unbound polymer and residual crosslinking agent. The washing and centrifugation process was repeated four times using Isopar-G solvent to recover chemically purified black particles. The purified particles were dried in a vacuum oven at 60°C for 12 hours to obtain the final black electrophoretic particle powder.

[0191] Analysis of the manufactured black iron oxide particles confirmed that a thick polymer shell of approximately 10.5 wt% was formed on the surface. Zeta potential measurements showed a stable strong positive charge of +85 mV in a non-polar dispersion medium.

[0192] In particular, the black particles to which the hybrid anchoring and crosslinking technology of the present invention was applied showed no permanent aggregation between particles when stored at high temperature (70°C) compared to conventional silane-based particles, and exhibited a significant effect of improving the loss of charge phenomenon by more than 30% when an electric field was applied. In addition, when an electrophoretic medium was formed by mixing with the previously prepared white particles, clear black and white contrast without aggregation between particles was achieved thanks to the different charge polarities and robust shell structure.

[0193] [Preparation Example 3] Preparation of Cyan Color Particles

[0194] A third type of cyan color electrophoretic particle, having a high-density graft polymer and a surface network cross-linking structure based on the organic pigment copper phthalocyanine, was manufactured by the following process.

[0195] 1. Surface pretreatment and inorganic coating process of cyanide pigment

[0196] Since organic pigments have a low surface hydroxyl (-OH) density, making it difficult to secure phosphonic acid bonding strength, a pretreatment process was performed to form a thin metal oxide layer on the surface of the pigment.

[0197] First, 100g of copper phthalocyanine (average particle size 180nm), a cyanide pigment, was dispersed in 800g of isopropanol. Then, 10g of tetraethoxysilane (TEOS) and water ammonia were added to induce a sol-gel (Stober) reaction, thereby uniformly coating the surface of the cyanide pigment with a silica (SiO2) layer approximately 5nm thick. Through this, abundant hydroxyl sites capable of hybrid anchoring were secured.

[0198] 2. Synthesis of a functionally integrated graft copolymer for cyanide (first compound)

[0199] To maintain high clarity and high-speed behavior of cyanide particles, an ionic liquid residue-based graft copolymer with maximized charge density was synthesized in advance.

[0200] 400 g of methyl ethyl ketone (MEK) was added to a reactor as a solvent. To this, 6 g of vinylbenzylphosphonic acid as a binding monomer, 20 g of 1-vinyl-3-alkylimidazolium bis(trifluoromethanesulfonyl)imide as a charging monomer, and 60 g of perfluoropolyether (PFPE) acrylate (Mw 1,500) as a dispersion macromonomer were mixed and added. Additionally, 4 g of hydroxyethyl methacrylate (HEMA) was added for the crosslinking reaction.

[0201] 0.8 g of AIBN, a polymerization initiator, was added, and polymerization was carried out at 75°C for 14 hours under a nitrogen atmosphere. After the reaction was finished, the solution was cooled and reprecipitated in excess ether to obtain a pure graft copolymer (Mw approximately 48,000).

[0202] 3. Surface Hybrid Anchoring Process of Cyanide Particles

[0203] A process was performed to chemically bond a synthesized graft polymer to the surface of a silica-coated cyanide pigment.

[0204] 100g of pre-treated cyanide pigment was added to 600g of anhydrous toluene and subjected to ultrasonic dispersion treatment. 18g of the cyanide graft copolymer synthesized above was added to this, and a reflux reaction was continued at 115°C for 24 hours. During this process, the phosphonic acid residues of the polymer reacted with hydroxyl groups and silicon ions on the surface of the silica coating layer to form Si-OP type polyvalent covalent bonds, thereby constructing a high-density functional shell layer on the organic pigment core.

[0205] 4. Process for forming a surface cross-linked network (second compound)

[0206] A crosslinking process was performed to completely block pigment leaching and increase the structural strength of the shell.

[0207] 1.2 g of toluene diisocyanate (TDI) was added as the second compound, a crosslinking agent, to the anchored suspension. The reaction was carried out by stirring at 80°C for 6 hours to induce urethane bonding between the hydroxyl groups of the graft main chain and the isocyanate groups of the crosslinking agent. Through this, an elastic network crosslinking structure was completed that encases the entire cyanide particle.

[0208] 5. Purification and Final Mediation Process

[0209] The reaction product was centrifuged at 12,000 rpm to remove the supernatant, and the washing process was repeated at least four times using Isopar-G. The final purified cyanide particles were dried in a vacuum oven at 50°C for 15 hours to be recovered in powder form, or redispersed in silicone oil containing the dispersant OLOA 11000 to prepare a cyanide electrophoresis medium.

[0210] Analysis of the manufactured cyanide particles confirmed that a robust polymer cross-linked shell of approximately 9.2 wt% was formed on the surface while the vivid color of the organic pigment remained unchanged. Zeta potential measurements showed a stable, very high positive charge of +92 mV in a non-polar medium.

[0211] In particular, the cyan particles to which the inorganic coating and hybrid anchoring technology of the present invention were applied did not exhibit any 'solvent leaching' phenomenon characteristic of organic pigments, and maintained a rapid response speed without shell peeling even when a repeated electric field was applied. In addition, when operated in combination with ultra-strong negative charge white particles, excellent image stability was demonstrated, in which the cyan color remained clear without spreading even after the power was turned off.

[0212] [Preparation Example 4] Preparation of Magenta Color Particles

[0213] Type 4 magenta color electrophoretic particles, based on the organic pigment quinacridone and equipped with a high-density graft polymer and a surface network cross-linking structure, were manufactured by the following process.

[0214] 1. Surface Silica Coating and Activation Process of Magenta Pigment

[0215] A pretreatment process was performed to form an inorganic insulating layer on the surface of the pigment to ensure reactivity between the organic pigment core and the phosphonic acid bonding part.

[0216] First, 100 g of quinacridone (average particle size 220 nm), a magenta pigment, was added to 700 g of isopropanol and stirred at high shear for 2 hours. Then, 12 g of tetraethoxysilane (TEOS), a silica precursor, and ammonia water for catalysis were added, and the sol-gel reaction was maintained for 12 hours.

[0217] Through this, a silica (SiO2) thin film with a thickness of about 6 nm was uniformly formed on the surface of the magenta pigment, and high-density hydroxyl (-OH) sites were exposed on the surface for the subsequent hybrid anchoring process.

[0218] 2. Synthesis of a functionally integrated graft copolymer for magenta (first compound)

[0219] To impart optimized dispersibility and charging properties to magenta particles, a graft polymer in which ionic functional groups and long-chain dispersion chains are integrated within the main chain was synthesized in advance.

[0220] 300 g of methyl ethyl ketone (MEK) was added to the reactor as a solvent. To this, 5 g of 2-methacryloyloxyethyl phosphate as a binding monomer, 12 g of 1-vinyl-3-butylimidazolium bis(trifluoromethanesulfonyl)imide as a charged monomer for imparting a strong positive charge, and 45 g of polydimethylsiloxane (PDMS) acrylate (Mw 5,000) and 25 g of perfluoropolyether (PFPE) acrylate (Mw 2,000) as dispersion macromonomers were mixed and added. Additionally, 4 g of glycidyl methacrylate was added to provide functional groups for shell crosslinking.

[0221] 0.5 g of AIBN, a polymerization initiator, was added, and polymerization was carried out at a temperature of 80°C for 12 hours under a nitrogen atmosphere. After the reaction was completed, the mixture was reprecipitated in hexane to obtain a graft copolymer for magenta with a weight average molecular weight (Mw) of approximately 55,000.

[0222] 3. Surface Hybrid Anchoring Process of Magenta Particles

[0223] A process was performed to chemically fix the synthesized graft polymer onto the surface of the pretreated magenta pigment.

[0224] 100g of silica-coated magenta pigment was added to 500g of anhydrous toluene and subjected to high-power ultrasonic dispersion treatment for 1.5 hours. 16g of the magenta graft copolymer synthesized above was added to the dispersion. The temperature of the reaction system was raised to 110℃ and the reflux reaction was continued for 20 hours. During this process, the phosphate residues of the polymer main chain formed strong polylocerate covalent bonds with the hydroxyl groups on the silica surface, thereby constructing an organic shell layer with maximized peel resistance on the surface of the pigment particles.

[0225] 4. Process for forming a surface cross-linked network (second compound)

[0226] A crosslinking process was performed to reinforce the physical strength of the polymer shell and to stably maintain charged ions.

[0227] After adjusting the temperature of the suspension, upon completion of the anchoring reaction, to 85°C, 1.8 g of trimethylolpropane triglycidyl ether was added as the second compound, a crosslinking agent. The reaction was carried out with additional stirring for 5 hours to form a dense shell-crosslinking structure that sterically connects the graft main chains. This crosslinking structure inhibited swelling of the pigment caused by the penetration of an external solvent and ensured the structural integrity of the shell.

[0228] 5. Purification and Final Mediation Process

[0229] Washing and concentration processes were performed to increase the purity of the manufactured magenta particles.

[0230] The reaction product was centrifuged at 12,000 rpm for 30 minutes to remove the supernatant, and unreacted materials and impurities were removed by washing four times with Isopar-L solvent. The purified magenta particles were dried in a vacuum oven at 60°C for 12 hours to be recovered in powder form, or the magenta electrophoresis medium was completed by adjusting the solid content and dispersing them in a non-polar dispersion medium.

[0231] Thermogravimetric analysis (TGA) of the prepared magenta particles confirmed that a high-density cross-linked polymer shell of approximately 8.8 wt% was formed on the pigment surface. Zeta potential measurements showed a stable positive charge of +72 mV in a non-polar medium.

[0232] In particular, the magenta particles to which the hybrid bonding system of the present invention was applied showed a significant effect in which the charge attenuation phenomenon was reduced by more than 35% compared to the conventional block copolymer method in a repeated driving test. In addition, excellent bistable was demonstrated in which the magenta color maintained its initial concentration for a long time without bleeding even after the power was turned off, confirming that it is a key material for realizing high-quality multi-color displays.

[0233] [Preparation Example 5] Preparation of Yellow Color Particles

[0234] Type 5 yellow color electrophoretic particles, based on the organic pigment isoindoline and equipped with a high-density graft polymer and a surface network cross-linking structure, were manufactured using the following process.

[0235] 1. Surface silica coating and activation process of yellow pigment

[0236] Inorganic coating pretreatment was performed to compensate for the low surface activity of organic pigments and to create strong reaction sites with phosphonic acid binding sites.

[0237] First, 100g of isoindoline (average particle size 200nm), a yellow organic pigment, was added to 800g of isopropanol and strongly dispersed for 3 hours. Then, 14g of tetraethoxysilane (TEOS), a silica precursor, and ammonia water for catalysis were added, and the sol-gel reaction was continued for 16 hours. Through this process, a silica (SiO2) thin film approximately 8nm thick was formed on the surface of the yellow pigment, and through washing and drying processes, an abundant supply of hydroxyl groups (-OH) necessary for hybrid anchoring was secured on the surface.

[0238] 2. Synthesis of graft copolymer for functionally integrated yellow (first compound)

[0239] To impart dispersion stability and precise charging characteristics in a non-polar medium, a graft polymer containing charged ionic liquid residues and long-chain alkyl dispersion chains was synthesized in advance.

[0240] 350 g of methyl ethyl ketone (MEK) was added to a reactor as a solvent. To this, 4 g of vinylbenzylphosphonic acid as a binding monomer, 12 g of 1-methyl-4-vinylpyridinium bis(trifluoromethanesulfonyl)imide as a charging monomer, and 60 g of carbon-22 behenyl acrylate and 20 g of perfluoropolyether (PFPE) acrylate (Mw 2,000) as dispersion macromonomers were mixed and added. Additionally, 4 g of hydroxyethyl methacrylate (HEMA) was added to provide a crosslinking reaction site.

[0241] 0.7 g of AIBN, a polymerization initiator, was added, and polymerization was carried out at 80°C for 12 hours under a nitrogen atmosphere. After the reaction was completed, the solution was reprecipitated in excess methanol to remove unreacted materials, thereby obtaining a graft copolymer for yellow with a weight average molecular weight (Mw) of about 50,000.

[0242] 3. Surface Hybrid Anchoring Process of Yellow Particles

[0243] A process was performed to chemically bond a synthesized graft polymer to the surface of a silica-coated yellow pigment.

[0244] 100g of pre-treated yellow pigment was added to 600g of anhydrous toluene and dispersed into primary particles by high-power ultrasonic dispersion treatment. 17g of the yellow graft copolymer synthesized above was added to this, and the temperature of the reaction system was raised to 110℃ and the reflux reaction was continued for 22 hours. During this process, phosphonic acid residues of the polymer main chain reacted with hydroxyl groups on the silica surface to form strong Si-OP polylocerate covalent bonds, thereby constructing a high-density functional polymer shell on the surface of the pigment particles.

[0245] 4. Process for forming a surface cross-linked network (second compound)

[0246] A crosslinking process was performed to increase the mechanical strength of the polymer shell and ensure charge stability during repeated operation.

[0247] After adjusting the temperature of the suspension, in which the anchoring reaction was completed, to 80°C, 1.6 g of hexamethylene diisocyanate (HDI) was added as the second compound, a crosslinking agent.

[0248] A small amount of dibutyltin dilaurate was added as a reaction catalyst and stirred for 6 hours. Through this, crosslinking agent molecules connected the hydroxyl groups of the graft main chain with urethane bonds, thereby completing an elastic shell-crosslinking structure that tightly encases the entire yellow pigment.

[0249] 5. Purification and Final Mediation Process

[0250] A high-purity purification process was performed to increase the purity of the manufactured yellow particles.

[0251] The reaction product was centrifuged at 12,000 rpm for 30 minutes to remove the supernatant, and the washing and centrifugation process was repeated 5 times using Isopar-G solvent. The purified yellow particles were dried in a vacuum oven at 60°C for 12 hours to obtain the final yellow electrophoretic particle powder.

[0252] Analysis of the manufactured yellow particles confirmed that a rigid cross-linked polymer shell of approximately 9.5 wt% was formed on the surface. Zeta potential measurements showed a stable negative charge of -68 mV in a non-polar dispersion medium.

[0253] In particular, the yellow particles with the shell cross-linked structure of the present invention showed a significant effect in which particle aggregation was reduced by more than 40% compared to the conventional block copolymer method in a high-temperature (70℃) accelerated test. In addition, excellent bistable was demonstrated in which almost no change in the concentration of the yellow color was observed even after the power was turned off, thereby securing optimal behavioral characteristics for realizing a high-reliability multicolor electrophoretic display device.

[0254] VIII. Preparation of Microcapsules

[0255] [Preparation Example 6]

[0256] To complete the technical configuration of the present invention, microcapsules containing high-performance charged particles prepared in each of Preparation Examples 1 to 5 were prepared using the following complex coacervation process.

[0257] 1. Preparation of Electrophoresis Internal Fluid

[0258] To prepare the electrophoretic fluid that serves as the core of the microcapsules, 200g of Isopar M, a non-polar hydrocarbon solvent, was introduced into a reactor. To this, 60g of the white particles of Preparation Example 1, 10g of the black iron oxide particles of Preparation Example 2, and 5g each of the cyan, magenta, and yellow particles of Preparation Examples 3 to 5 were mixed and added. To stabilize the charged state of the particles within the dispersion medium, 2.5g of polyisobutylene succinimide (OLOA 11000), a charge control agent (CCA), was additionally added. The mixture was high-shear dispersed using a homogenizer at a speed of 5,000 rpm for 1 hour, thereby completing a uniform electrophoretic internal solution in which particle size variation and the unique shell structure of each particle were maintained.

[0259] 2. Preparation of the Aqueous Phase and Emulsification

[0260] An aqueous solution was prepared to form the outer wall of the capsule. 20 g of Type 1 gelatin and 20 g of gum arabic, which serve as wall materials, were added to 1,000 mL of distilled water and completely dissolved at 50°C. The resulting mixed aqueous solution was maintained at 45°C and gently stirred using an impeller stirrer. After slowly adding the prepared electrophoretic internal solution to the prepared aqueous continuous phase, the homogenizer speed was increased to 3,500 rpm to induce the oily internal solution to disperse into fine droplets within the aqueous solution. The droplet size was monitored in real time using an optical microscope, and the stirring speed was fixed when the average particle size reached the range of 50 μm to 60 μm.

[0261] 3. Induction of complex coacervation and wall formation

[0262] Phase separation was induced to deposit a polymer wall material on the surface of a droplet. A 10% aqueous acetic acid solution was precisely added dropwise to adjust the pH of the mixture to 4.5. As the pH decreased, positively charged gelatin and negatively charged gum arabic electrostatically bonded to form coacervates, and it was confirmed that these formed a transparent initial wall film by enveloping the surface of the hydrophobic electrophoretic fluid droplet.

[0263] 4. Cooling and Wall Hardening Process

[0264] To ensure structural stability of the wall membrane, the temperature of the reaction system was slowly cooled to below 10°C. The cooling state was maintained for approximately 1.5 hours to induce a sol-gel transition of gelatin, thereby primarily fixing the wall membrane structure. Subsequently, 5 mL of glutaraldehyde, a crosslinking agent, was added to increase the chemical strength of the wall membrane. The crosslinking reaction was carried out at 10°C for 2 hours, after which the temperature was raised again to 25°C and maintained for 10 hours to complete a hard and dense microcapsule outer wall.

[0265] 5. Secondary curing reaction and stabilization

[0266] Secondary curing was performed to further reinforce the mechanical strength of the microcapsule outer wall and optimize surface polarity. 10 g of CMC (Carboxymethylcellulose sodium salt) was added to the microcapsule suspension after the crosslinking reaction was completed. Subsequently, the reaction system was heated to 40°C and reacted for 2 hours, and the mixture was sufficiently stirred at room temperature for more than 12 hours to obtain final microcapsules with improved outer wall density and strength.

[0267] 6. Washing and Particle Size Sorting

[0268] The reaction-completed microcapsule suspension was passed sequentially through 100 μm and 30 μm standard sieves to remove coarse particles and fine dust. The selected microcapsules were washed four times repeatedly with distilled water to completely remove residual charge regulators and unreacted wall material components. Finally, the precipitated microcapsules were recovered and prepared into a capsule slurry with a solid content of 40%.

[0269] The microcapsules manufactured through the above process exhibited sufficient mechanical strength to withstand the shear force of the subsequent film coating process without breakage. In particular, it was confirmed that the white, black, and three types of colored particles inside the capsules existed independently without mutual interference in the fluid thanks to the graft structure and cross-linked network shell of the present invention, and possessed electrical characteristics that behaved rapidly and precisely according to the zeta potential of each particle upon the application of an electric field.

[0270] IX. Example of Electrophoretic Film Preparation

[0271] [Example 1] An electrophoretic film applicable to an actual display device was manufactured using the following process by utilizing microcapsules filled with high-performance charged particles of the present invention.

[0272] 1. Preparation of Microcapsule Coating Slurry

[0273] First, 100g of the microcapsule slurry with a solid content of 40% obtained in Preparation Example 6 was placed into a stainless steel mixing container. To this, 10g of a water-dispersible polyurethane (PUD) nanoparticle dispersion (based on solid content) was mixed as a binder. 0.1g of a fluorine-based wetting agent was added to ensure film smoothness during the coating process, and the mixture was gently stirred for 30 minutes using a low-speed impeller of 100 rpm or less to prevent damage to the outer walls of the microcapsules. Through this, a coating slurry was completed in which the microcapsules were uniformly dispersed within the binder medium.

[0274] 2. Precision coating process on a transparent electrode substrate

[0275] A PET film with Indium Tin Oxide (ITO) deposited thereon having a sheet resistance of 100 Ω / sq was prepared as the upper electrode substrate. The prepared slurry was precisely applied to the conductive surface of the prepared ITO-PET film using a comma coater. At this time, the gap of the coating blade was controlled in micron units so that the thickness of the display layer after drying was approximately 35 μm. This thickness was the optimal value for the microcapsules (approximately 50-60 μm) to be properly compressed during the drying process to form a dense monolayer on the substrate.

[0276] 3. Step-by-step drying and shell-network formation

[0277] The coated film was passed through a multi-stage hot air dryer maintained at a temperature of 70°C for 3 minutes. As moisture evaporated, PUD binder nanoparticles densely infiltrated into the gaps between the microcapsules, physically fixing the capsules to the substrate while simultaneously forming a three-dimensional point contact network. Microscopic observation after drying confirmed that a uniform display layer was formed without microcapsule breakage or voids.

[0278] 4. Lamination and Film Completion

[0279] An additional process for protection and adhesion was performed on the upper surface of the dried display layer (the surface in contact with the lower electrode). A 25 μm thick thermoplastic polyurethane (TPU)-based lamination adhesive film was placed on the display layer, and a heat-press lamination process using a heating roller was performed. Finally, a separate PET film for back protection was laminated to complete the manufacture of the final electrophoretic film.

[0280] 5. Performance evaluation of manufacturing results

[0281] The completed electrophoretic film was cut into a specific size, connected to a test driving circuit, and its optical properties were evaluated by applying a voltage of ±15V. Thanks to the graft polymer and surface crosslinking technology of the present invention, clear images with a contrast ratio (CR) of 15:1 or higher were displayed even in the film state. In particular, thanks to the charge stability of the crosslinked shell structure, lateral charge spreading was blocked during image switching, resulting in excellent visibility at pixel boundaries. Furthermore, strong bistability was demonstrated by maintaining the initial reflectance stably for more than 12 hours even after the power was turned off. This was the result of structurally resolving the charge loss and afterimage problems associated with conventional block copolymer-based films.

[0282] X. Preparation Example and Characterization of Electrophoretic Display Device

[0283] [Example 2] The electrophoretic film prepared in Example 1 was integrated with a driving substrate to complete a display device.

[0284] First, a glass substrate was prepared with a thin-film transistor (TFT) array formed thereon capable of individual pixel control as a backplane. After washing with isopropanol to remove foreign substances from the surface of the substrate, oxygen plasma treatment was performed to increase the insulation between pixels and prevent lateral charge spreading, thereby adjusting the surface energy to 70 mN / m or higher.

[0285] After precisely cutting the film of Example 1 to match the substrate specifications, the back-side protective PET film was removed to align the exposed adhesive layer surface with the electrode surface of the driving substrate. Subsequently, heat-press lamination was performed using a roll laminator at a temperature of 90°C and a pressure of 0.3 MPa. To prevent moisture penetration, a high-barrier epoxy resin was applied to the side edges of the laminated panel, and then edge sealing was completed using a UV curing system (365 nm, 3,000 mJ / cm²).

[0286] 2. Driving Circuit Connection and System Construction

[0287] The common electrode (ITO) at the top of the film and the electrode terminal at the bottom of the driving substrate were connected to the driving circuit using an anisotropic conductive film (ACF). A flexible circuit board (FPC) equipped with a driving IC was bonded, and a proprietary waveform algorithm capable of precisely controlling voltage magnitude and pulse width was incorporated into the system.

[0288] 3. Performance Evaluation and Verification of Effectiveness of Display Devices

[0289] The technical performance of the present invention was evaluated from various angles by applying a DC voltage of ±15V to the completed device.

[0290] a. Optical properties (contrast ratio and color purity)

[0291] As a result of measurement, the contrast ratio (CR) using the difference in luminance between the white state and the black state was recorded at 15:1 or higher. In particular, thanks to the graft polymer with the ionic liquid residue introduced in the present invention, the particle migration speed was improved by more than 30% compared to conventional technology, resulting in clear image quality without color mixing even during complex multi-color image switching.

[0292] B. Prevention of ghosting and crosstalk

[0293] Repetitive driving tests were conducted to verify the effect of the surface network crosslinking structure (second compound). Observing the phenomenon of charge spreading sideways at pixel boundaries after image switching, the interface blurring observed in conventional block copolymer methods was almost entirely absent. This proved that the crosslinked shell structure physically trapped the charge on the particle surface, blocking lateral movement.

[0294] C. Bistability and Memory Characteristics:

[0295] After writing an image, the power was completely cut off, and the change in reflectance over time was measured. The display device of the present invention exhibited excellent memory characteristics, maintaining more than 98% of the initial reflectance even after 12 hours had elapsed since the power was cut off. This was the result of charge leakage being fundamentally suppressed due to the strong ion confinement effect inside the shell.

[0296] 4. Long-term reliability and harsh condition testing

[0297] Operational reliability was evaluated after storage for 1,000 hours in an environment of high temperature at 60°C and 90% relative humidity. Thanks to the strong phosphonic acid-based hybrid anchoring technology, no polymer shell delamination or particle aggregation was observed, and the initial response speed and contrast ratio were maintained without change in driving voltage.

[0298] The electrophoretic display device fabricated through Example 2 improved the process complexity of the conventional three-color sequential combination system, and at the same time, significantly improved the charge loss phenomenon through a hybrid network-based shell structure (improved by more than 30% compared to the conventional one). As a result, it was finally confirmed that this is a next-generation display technology capable of high contrast ratio, high reliability, and ultra-long image retention in a low-voltage driving environment.

[0299] XII. Performance Evaluation and Verification of Effectiveness

[0300] Test examples were conducted to demonstrate the significant effects and numerical limitations of the graft polymer structure, phosphonic acid hybrid anchoring, ionic liquid residue, and surface crosslinking network technology of the present invention compared to conventional technology.

[0301] Table 1. Composition of test samples

[0302]

[0303] Three comparative examples reproducing conventional technology and five examples applying the composition of the present invention step by step were prepared. The base particles were standardized to titanium dioxide with an average particle size of 250 nm.

[0305] Test Examples and Result Analysis

[0306] [Test Example 1] Test for precise control of zeta potential and maximization of charge

[0307] Test Objective: To verify the effect of introducing ionic liquid residues on charge quantity and charge stability compared to conventional polarizers.

[0308] Test design: After dispersing each particle in Isopar M, the initial charge amount is measured using a zeta potential analyzer, and the charge retention rate is measured after 100 hours of operation under an electric field of ±15V.

[0309] Table 2. Test Results for Precise Control of Zeta Potential and Maximization of Charge

[0310]

[0311] Analysis of measurement results: Example 1 of the present invention (an ionic liquid residue-introduced graft polymer) recorded an initial zeta potential of -98.4 mV, showing a charging performance improved by approximately 231% compared to -42.5 mV of Comparative Example 1 (combination of linear block and low molecular weight charge agent), which is a conventional technology. In particular, Example 4, which increased the charge density, reached up to -125.2 mV, breaking through the limit of the amount of charge achievable in a non-polar medium.

[0312] These significant differences stem from fundamental changes in the charging mechanism. The low-molecular-weight charging agent of Comparative Example 1 has structural limitations, such as competing with the dispersant for binding sites on the particle surface and easily desorbing. In contrast, the embodiments of the present invention maximized the degree of charge dissociation by directly incorporating ionic liquid residues, such as imidazolium salts, into the graft polymer main chain. In the measurement of retention rate after 100 hours of continuous operation, Example 1 showed high stability of 96.8%, whereas Comparative Example 1 plummeted to 78.2% due to charge leakage and ion desorption. This demonstrates that the present invention is an optimal charging system for realizing low-voltage operation and high-speed response displays.

[0313] [Test Example 2] Peeling resistance and chemical durability test of polymer shell

[0314] Test Objective: To demonstrate whether phosphonic acid polydentate bonds and surface cross-linking structures prevent physical detachment of the shell under electric field stress.

[0315] Test design: After performing an accelerated exfoliation test by applying high-power ultrasound (40 kHz, 300 W) to the dispersion for 5 hours, the particles are recovered and the residual polymer content (wt%) is measured by TGA (thermogravimetric analysis).

[0316] Table 3. Test results of peel resistance and chemical durability of polymer shells

[0317]

[0318] Analysis of measurement results: After an accelerated peeling test using high-power ultrasound, the amount of polymer remaining on the particle surface was analyzed by TGA, and the polymer loss rate of Example 1 was only 2.8%. This stands in stark contrast to Comparative Example 1, which showed extreme peeling of 38.8% under the same conditions, and Comparative Example 3 (using a graft polymer but with silane bonding), which showed peeling of 26.1%.

[0319] The resulting data suggests that the combination of 'phosphonic acid polydentate bonds' and 'surface network crosslinking' is essential for maintaining the physical integrity of the shell. The fact that even Comparative Example 3 showed a high peeling rate demonstrates that silane-based single bonds (-Si-O-) are vulnerable to mechanical shock and trace amounts of moisture. On the other hand, Example 1 encapsulated the entire particle into a robust network structure through strong anchoring of phosphonic acid residues and cross-linking between shell chains by a crosslinking agent. As a result, extreme durability was secured, ensuring that the shell is maintained even under repeated electric field stress without any aggregation between particles.

[0320] [Test Example 3] Dispersion stability test according to dispersion part (side chain) Mw and structure

[0321] Test Objective: To verify the critical significance of the molecular weight and topology of graft side chains in blocking aggregation by maintaining inter-particle distance.

[0322] Test design: Quantify the steric hindrance effect by measuring the change in sedimentation height and particle size (D50) for 1,000 hours in a high temperature environment of 60℃.

[0323] Table 4. Dispersion stability test results according to dispersion part (side chain) Mw and structure

[0324]

[0325] Analysis of measurement results: As a result of evaluating high-temperature storage stability according to the number average molecular weight (Mw) of the graft side chain (second monomer unit), Example 1 with an Mw of 2,000 and Example 5 with an Mw of 3,500 showed extremely small changes in particle size of approximately 5 nm even after 1,000 hours at 60°C, and maintained an excellent dispersion state with a precipitation height ratio of over 92%.

[0326] On the other hand, Example 2, in which the side chain Mw was lowered to 450, appeared to be dispersed at the beginning of the experiment, but after being left at high temperature, the particle size increased rapidly from 275 nm to 390 nm, and the precipitation height ratio dropped to 62%. This means that when the molecular weight of the side chain is less than 500, the excluded volume formed by the polymer chain in a non-polar solvent is not sufficient to offset the van der Waals forces between particles. Therefore, the numerical limitation of 'side chain Mw 500 or higher' has been proven to be a critical point for blocking spontaneous particle aggregation and ensuring high-temperature storage stability.

[0327] [Test Example 4] Bistability and Image Retention Test

[0328] Test Objective: Evaluate the ability of a surface network cross-linked structure to prevent charge leakage and maintain images after power interruption.

[0329] Test Design: After displaying the image, the power is cut off, and the rate of contrast ratio decay over time is measured.

[0330] Table 5. Bistability and Image Retention Test Results

[0331]

[0332] Analysis of measurement results: In the contrast ratio (CR) retention rate test over time after power cut-off, Example 1, which has a surface cross-linked structure, showed excellent performance by maintaining 97.5% of the initial image even after 12 hours. On the other hand, Comparative Example 1, a conventional technology, dropped to 82.5% after just 1 hour and further to 45.2% after 12 hours, making image retention virtually impossible.

[0333] The comparison result with Example 3 (retention rate 72.0%), which lacks a cross-linked structure, clearly elucidates the role of the cross-linked network. The cross-linked network structure inside the shell induces an 'ion trapping' effect that physically blocks the path of charged ions on the surface diffusing into the solvent. As a result, even when the electric field is removed, the charge of the particles is not lost and remains strongly adhered to the electrode surface, achieving a remarkable effect of improving image retention ability by more than twofold compared to conventional technology.

[0334] As a result of the test, the embodiments of the present invention demonstrated significant effects in all evaluation indicators compared to conventional technology, based on a comprehensive analysis of precise performance evaluation data.

[0335] First, regarding the charge performance of the particles, the present invention, which introduces ionic liquid residues, showed a significant reduction in zeta potential from the conventional -42.5mV to -98.4mV, resulting in an improvement in charge amount of approximately 230%. This means that electrical characteristics favorable for low-voltage driving and high-speed response have been perfectly established through a main chain structure in which the degree of ion dissociation is maximized within a non-polar medium.

[0336] Second, in the peel resistance test evaluating the physical durability of the polymer shell, the conventional technology showed a high polymer loss rate of 38.8% under electric field stress, whereas the present invention recorded an extremely low loss rate of 2.8%, realizing a durability enhancement of more than 13 times. This result demonstrates that the phosphonic acid-based polyvalent covalent bond and the inter-chain network cross-linking structure combined to increase the chemical fixation strength of the shell to a permanent level.

[0337] Third, as a result of confirming the dispersion retention power in a high-temperature environment, while the conventional technology exhibited a severe aggregation phenomenon in which the particle size (D50) increased rapidly to 185 nm after storage at 60°C, the present invention showed a change in particle size of only 6 nm, effectively completely solving the problem of spontaneous aggregation. This suggests that the critical exclusion volume effect provided by the graft side chain within a specific molecular weight range is stably maintained even at high temperatures.

[0338] Fourth, in the evaluation of image retention rate, which is the actual driving performance of the display, the conventional technology maintained only 45.2% of the initial image after 12 hours of power cut-off, resulting in a rapid decline in visibility, whereas the present invention maintained a high contrast ratio of 97.5% and achieved a bistability value improved by approximately 2.1 times. This is because the network cross-linked shell physically traps the outflow of charged ions, enabling long-term image display without power consumption.

Claims

Claim 1 An electrophoretic display device comprising: at least one substrate having a common electrode and a driving electrode formed thereon; an electrophoretic film disposed between the substrates; and an electrophoretic medium sealed within the electrophoretic film, wherein the electrophoretic medium comprises a nonpolar dispersion medium and charged electrophoretic particles, and the electrophoretic particles comprise a base particle having a first functional group on its surface, a first compound and a second compound bonded to the base particle, wherein the first compound is a graft polymer copolymerized with a charged monomer unit comprising a phosphonic acid residue forming a multidentate bonding with the first functional group, a side-chain macromonomer unit providing dispersibility, and an ionic liquid residue, and the second compound is a crosslinking agent that chemically links the main chains of the first compound to form a shell cross-linking structure over the entire surface of the particle. Claim 2 The electrophoretic display device according to claim 1, wherein the base particle is at least one of titanium dioxide (TiO2), titanium nitride (TiN), iron oxide (Fe2O3, Fe3O4), or an organic pigment coated with silica, and the first functional group is a hydroxyl group (-OH) or a carboxyl group (-COOH) on the surface of the particle. Claim 3 An electrophoretic display device according to claim 1, wherein the phosphonic acid residue of the first compound is derived from at least one monomer selected from the group consisting of vinylphosphonic acid, 2-methacryloyloxyethyl phosphate, and vinylbenzylphosphonic acid, and forms a POM (M is a metal element) bond with the surface of the base particle to improve shell peeling resistance by more than 10 times compared to conventional silane bonds. Claim 4 An electrophoretic display device according to claim 1, wherein the side-chain macromonomer unit of the first compound is at least one selected from the group consisting of perfluoropolyether (PFPE), polydimethylsiloxane (PDMS), and long-chain alkyl acrylate having 12 or more carbon atoms, with a number average molecular weight (Mw) in the range of 500 to 5,000, and provides a critical exclusion volume effect that blocks inter-particle aggregation within the said molecular weight range. Claim 5 An electrophoretic display device according to claim 1, wherein the charged monomer unit of the first compound comprises at least one ionic liquid residue selected from the group consisting of imidazolium salt, pyridinium salt, and quaternary ammonium salt, and the zeta potential of the particle is linearly controlled within the range of ±20mV to ±120mV through density control of the ionic liquid residue. Claim 6 An electrophoretic display device according to claim 1, wherein the second compound is a low-molecular-weight compound containing two or more epoxy groups, isocyanate groups, or aziridine residues within the molecule, and the network structure formed by the crosslinking agent physically blocks the outflow of charged ions to improve the phenomenon of charge loss. Claim 7 An electrophoretic particle included in the electrophoretic display device of claim 1, characterized by comprising: a base particle having a first functional group on its surface; a graft polymer having a charged portion including a main chain having a phosphonic acid residue bonded to the surface of the base particle, a side chain providing dispersibility, and an ionic liquid residue integrated within a single molecule; and a network cross-linking structure that interweaves the main chains of the graft polymer on the surface. Claim 8 Electrophoretic particles according to claim 7; and an electrophoretic medium characterized by comprising a nonpolar dispersion medium comprising silicone oil, hydrocarbon oil, or fluorine oil. Claim 9 An electrophoretic medium according to claim 8, characterized in that the electrophoretic particles in the electrophoretic medium have dispersion stability such that the change in the initial average particle size (D50) is maintained within 5% even after being left at 60°C for 1,000 hours due to the network cross-linking structure. Claim 10 An electrophoretic film characterized by comprising a structure in which the electrophoretic medium according to claim 8 is filled within a plurality of microcapsules or sealed within a microcell structure formed on a substrate. Claim 11 An electrophoretic film according to claim 10, characterized in that the network cross-linked shell of the electrophoretic particles on the inner side of the outer wall of the microcapsule or microcell prevents electrical adhesion between particles, thereby blocking crosstalk at the pixel boundary during image switching. Claim 12 An electrophoretic display device according to claim 1, characterized by having bistable such that the contrast ratio of a displayed image is maintained at 95% or higher of the initial value for more than 10 hours due to the synergistic effect of the high-density graft structure of the electrophoretic particle and the surface cross-linking network.

Citation Information

Patent Citations

  • Electrophoretic particle, method of producing electrophoretic particle, electrophoretic dispersion liquid, electrophoretic sheet, electrophoretic apparatus and electronic apparatus

    JP2013156381A

  • Microcapsule, electrophoretic display sheet, electrophoretic display device, and electronic apparatus

    US7457028B2